MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR FISIKA SISWA MELALUI PEMANFAATAN E-BOOK INTERAKTIF BERBASIS PROBLEM BASED LEARNING - Intan Irawati (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2023)
Abstract The research objective was to increase student activity and achievement during PJJ by using interactive e-book media in physics lessons. The research was conducted at MAN 15 Jakarta on 36 students of class XI IPA-3 for the 2020-2021 academic year. The waves e-book used in the study were compiled using a book creator application based on the PBL learning model. The type of research used is Classroom Action Research with the stages of planning, observation, implementation, and reflection. The research was conducted for two cycles with two meetings per cycle in March-April 2021. The instruments used included the KBM observation instrument, the student observation instrument, and the test instrument. The data obtained is displayed in tables and graphs and then analyzed descriptively. The results showed that after the action, the average student (66%) said they liked learning with e-book media and understood the material more than just discussions via wag and video conferencing. The effect that can be observed after learning using e-books is an increase in their activity during online learning activities. This student activity occurred during PJJ with the Wag platform (WhatsApp group) or via video conferencing. Students' activeness increased from cycle 1 to cycle 2, as seen from their questions and answers during discussions, group work, and assignment presentations. Student learning test scores increased from before the action to cycle one average up 23%, and from cycle 1 to cycle two increased by 51%. Student learning outcomes, even before the action and after the research, increased by 39.58. After cycle 1, the increase in learning outcomes was 18.97; after cycle 2, the increase was 20.61. This study recommends using interactive e-book media to improve student activities and learning outcomes in physics learning conducted online or blended learning. Abstrak Tujuan dari penelitian adalah meningkatkan keaktifan siswa dan hasil belajar pada saat PJJ dengan menggunakan media e-book interaktif pada pelajaran fisika. Penelitian dilakukan di MAN 15 Jakarta pada 36 siswa kelas XI IPA-3 tahun pelajaran 2020-2021. E-book Gelombang yang digunakan dalam penelitian disusun disusun dengan aplikasi book creator berbasis model pembelajaran PBL. Jenis penelitian yang digunakan merupakan Penelitian Tindakan Kelas dengan tahapan perencanaan, observasi, pelaksanaan dan refleksi. Penelitian dilakukan selama 2 siklus dengan 2 kali pertemuan setiap siklus pada bulan Maret-April 2021. Instrumen yang digunakan meliputi instrumen observasi KBM, instrumen observasi siswa dan instrumen tes. Data yang diperoleh ditampilkan dalam bentuk tabel dan grafik kemudian dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa setelah tindakan, rata-rata siswa (61%) menyatakan bahwa mereka suka belajar dengan media e-book dan lebih paham materi dari pada hanya dengan diskusi via grup WhatsApp dan video conference. Adapun keaktifan siswa meningkat dari siklus 1 ke siklus 2 terlihat dari tanya jawab mereka saat berdiskusi, bekerja kelompok, dan presentasi tugas yang diberikan. Skor tes belajar siswa meningkat dari sebelum tindakan ke siklus 1 rata-rata naik 23% dan dari siklus 1 ke siklus 2 meningkat 51%.  Hasil belajar siswa pun sebelum tindakan dan setelah penelitian mengalami peningkatan sebesar 39,58. Setelah siklus 1 kenaikan hasil belajar 18,97 dan setelah siklus 2 kenaikan 20,61. Penelitian ini merekomendasikan penggunakan media e-book interaktif untuk meningkatkan aktivitas dan hasil belajar siswa pada pembelajaran fisika yang dilakukan secara daring ataupun blended learning.